2009
DOI: 10.2202/1556-3758.1376
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Absorbent Materials in Evaporative Cooling System for the Storage of Fruits and Vegetables

Abstract: An experimental storage based on the principle of evaporative cooling was designed to evaluate the performance of three natural absorbent fiber materials to be used as cooling pads. The absorbent materials were jute, hessian and cotton waste. The performance criteria included cooling efficiency, material performance and total amount of heat load removed from the evaporative cooler. The results showed that under the no-load condition, the average cooling efficiency was highest for jute at 86.2%, compared to 76.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 3 publications
1
29
0
Order By: Relevance
“…Therefore, for a given size of cooler, lighter bulk weight would be handled the lesser the bulk density of the cooling pad. Olosunde et al (2009) used jute pad that was less dense (82.81 kg/kg) than the type used in this study (89.80 kg/kg) also whose water holding capacity was lower (1.762 kg/kg) than the type in this study (2.1 kg/kg) .…”
Section: Physical Properties Of Pad Materialsmentioning
confidence: 73%
See 2 more Smart Citations
“…Therefore, for a given size of cooler, lighter bulk weight would be handled the lesser the bulk density of the cooling pad. Olosunde et al (2009) used jute pad that was less dense (82.81 kg/kg) than the type used in this study (89.80 kg/kg) also whose water holding capacity was lower (1.762 kg/kg) than the type in this study (2.1 kg/kg) .…”
Section: Physical Properties Of Pad Materialsmentioning
confidence: 73%
“…Al-Sulaiman (2002) reported cooling efficiency of 62.1% with jute pad, 55.1, 49.5 and 38.9% with luffa, Aspen wood excelsior and palm fibers, respectively. Olosunde et al (2009) reported 86.2% cooling efficiency for jute pad. Gunhan et al (2007) reported a range of cooling efficiency for five different pads under different conditions: CELdek (46.1 to 78.5%); Volcanic tuff (68.0 to 77.9%); Fine pumice stones (77.7 to 90.6%), coarse pumice stones (56.1 to 72.1%); shading net (25.2 to 32.8%).…”
Section: Cooling Efficiency Of the Evaporative Cooling Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, some methods of preserving fruit http://dx.doi.org/10.1016/j.solener.2015.06.006 0038-092X/Ó 2015 Elsevier Ltd. All rights reserved. and vegetables, other than expensive electric powered refrigeration systems, such as storage in a ventilated shed, using zero energy storage based on an evaporative coolant system, waxing and hot water treatment have been found to be an efficient and economical means of reducing postharvest storage loss worldwide (Couey, 1989;Fallik et al, 1996;Olosunde, 2006;Lu et al, 2007;Sushmita et al, 2008;Islam and Morimoto, 2012). According to Dvizama (2010), the shelf life of fruit and vegetables is enhanced by minimizing deteriorative reactions, and availability for longer periods would reduce fluctuations in market supply and prices.…”
Section: Introductionmentioning
confidence: 99%
“…In this contest some methods of preservation of fruit and vegetables alternative to electric powered expensive refrigeration system like storage in ventilated shed, use of zero energy storage based on evaporative coolant system, waxing and hot water treatment has been found to be an efficient and economical means of reducing postharvest storage loss worldwide [7][8][9][10][11][12]. According to Dvizama [13], shelf life of fruit and vegetables are enhanced by minimizing deteriorative reactions and availability for longer periods would reduce fluctuation in market supply and prices.…”
Section: Introductionmentioning
confidence: 99%